A framework to guide research engagement in the policy process, with application to small-scale fisheries - Ratner, Blake D.; Dubois, Mark; Morrison, Tiffany H.; Tezzo, Xavier; Song, Andrew M.; Mbaru, Emmanuel; Chimatiro, Sloans K.; Cohen, Philippa J. (Resilience Alliance, Inc., 2022)
Research-engaged decision making and policy reform processes are critical to advancing resilience, adaptation, and transformation in social-ecological systems under stress. Here we propose a new conceptual framework to assess opportunities for research engagement in the policy process, building upon existing understandings of power dynamics and the political economy of policy reform. We retrospectively examine three cases of research engagement in small-scale fisheries policy and decision making, at national level (Myanmar) and at regional level (Pacific Islands region and sub-Saharan Africa), to illustrate application of the framework and highlight different modes of research engagement. We conclude with four principles for designing research to constructively and iteratively engage in policy and institutional reform: (a) nurture multi-stakeholder coalitions for change at different points in the policy cycle, (b) engage a range of forms and spaces of power, (c) embed research communications to support and respond to dialogue, and (d) employ evaluation in a cycle of action, learning, and adaptation. The framework and principles can be used to identify entry points for research engagement and to reflect critically upon the choices that researchers make as actors within complex processes of change.